"Only the intervenor cared": Tracing the neoliberalization of environmental policy in Wisconsin's Dairyland. (August 2022) - D'Onofrio, Sarah
Abstract: Drawing from Peck and Tickell's (2002) theory of roll-back and roll-out neoliberalism and Brenner et al.'s (2010) theory of variegated neoliberalism, this paper uses comparative historical analysis to understand how the state of Wisconsin suppressed its legacy of progressive environmentalism and embraced neoliberal policy over time. Specifically, this paper examines the rapid expansion of concentrated animal feeding operations (CAFOs) in Wisconsin's dairy industry since 1995. As these large CAFOs have grown in size, so have the social and environmental problems related to their use, including pollution of drinking water sources for rural communities. Based on analysis of newspaper articles between 1965-2010, I observed that that a turning point towards neoliberalism occurred with the demise of the Office of the Public Intervenor (OPI), a legally designated adversarial force unique to the state that was created in 1967 after a powerful coalition of environmental social movements defeated an attempt to merge the offices of development and environmental protection. Despite the continuous efforts of industry, the effort to weaken environmental regulations and institutions in Wisconsin failed not only in 1967, but in 1984 as well. However, by 1995, immediately after the passage of the North American Free Trade Agreement, the state switched their support from populist environmental social movements to industry. Through deregulation, elimination of the OPI, and the gradual dissolution of environmental social movements, the state of Wisconsin created the conditions that enabled CAFOs to expand without the "burden" of environmental regulation. Subsequently, through re-regulation, Wisconsinites lost access to legal remedies that could curb polluting practices of large CAFOs. This research is part of a larger project to understand the environmental impacts of regulatory failure in the Core as states in the Global North continue to adopt neoliberal environmental policy. Highlights: Industry in Wisconsin failed in their attempts to de/reregulate environmental regulationsuntil 1995. Deregulation included termination of the Public Intervenor (OPI)- an environmental watchdog agency created in 1967. De/reregulation led by the state encouraged the rapid growth of CAFOs despite the pollution they cause in rural communities.